ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA CALON NASABAH ASURANSI JIWA PT. PRUDENTIAL DI KABUPATEN MIMIKA - William Nugraha Rantetasak; Heppy Rubani; RULAN L. MANDUAPESSY (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the factors that influence the low demand for prospective customers of PT Prudential in Mimika Regency. The registrant data used in this study covers the period from 2019 to 2023, using the Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) analysis tools. The results of the factor analysis show that the most significant factors influencing the low demand for prospective customers are the price expectation and income variables. This study is expected to help PT. Prudential Mimika Regency understand the factors that influence the low demand for prospective customers.